A DFT Study on the Electronic Structures and Conducting Properties of Rubrene and its Derivatives in Organic Field-Effect Transistors - Huipeng Ma (Nature Portfolio, 2017)
Abstract We systematically studied the electronic structures and conducting properties of rubrene and its derivatives reported recently, and disscussed the influences of electron-withdrawing groups and chemical oxidation on the reorganization energies, crystal packing, electronic couplings, and charge injection barrier of rubrene. Hirshfeld surface analysis and quantum-chemical calculations revealed that the introduction of CF3 groups into rubrene decreases the H···H repulsive interaction and increases intermolecular F···H/H···F attractive interactions, which resulted in the tight packing arrangement and the increase of the electronic couplings, and finally cause the higer intrinsic hole-mobility in bis(trifluoromethyl)-dimethyl-rubrene crystal (μh = 19.2 cm2 V−1 s−1) than in rubrene crystal (μh = 15.8 cm2 V−1 s−1). In comparison, chemical oxidation reduces charge-carrier mobility of rubrene crystal by 2~4 orders of magnitude and increased the hole and electron injection barrier, which partly explains the rubrene-based field-effect transistor performance degrades upon exposure to air. Furthermore, we also discussed the influence of structural parameters of carbon nanotube (CNT) electrode on charge injection process, which suggests that the regulation of CNT diameters and increasing in thickness is an effective strategy to optimize CNT work functions and improve n-type OFET performances based on these organic materials.